Efektivitas Kombinasi Ekstrak Lidah Buaya dan Lidah Mertua Terhadap Mortalitas Larva Aedes aegypti - Handayani Narendo Putri; Dita Pratiwi Kusuma Wardani; Isna Hikmawati; Muhammad Luthfi Almanfaluthi (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
The Dengue Haemoragic Fever (DHF) vector control with synthetic larvicide has an impact on health and environmental problems, so alternative plant-based insecticides are needed. The study aims to determine the larvicidal effect of a combination with Aloe vera extract and Sansivieria trifasciata on the mortality of Aedes aegypti larvae. This study was conducted with experimental design by a post-test only with control groups design consisting of five groups. Two groups are positive control (1% temephos) and negative control (0% concentration). The other three groups served as a combination of Aloe vera extract and S. trifasciata Prain in ratio of 75%:25% (P1), 50%:50% (P2), and 25%:75% (P3). A total of 375 larvae were introduced in this study with three replications and with observation time of 30 minutes, 1 hour, 3 hours, 6 hours, 12 hours, 24 hours until totally died 100%. The mortality of Aedes aegypti larvae were analyzed by Kruskal Wallis and probit analysis to calculate LC50 and LC90. The larvae totally died 100% after 12 hours of exposure. There are significant differences in the mortality of Ae. aegypti larvae after administration of a combination with Aloe vera extract and S. trifasciata Prain. The P1 group (The combination with Aloe vera extract and S. trifasciata Prain with a ratio of 75%:25%) was the most effective in mortality of Ae. aegypti larvae. The LC50 value is 0.517% while the LC90 value is 2.121% within 6 hours. The combination group of Aloe vera extract and mother-in-law's tongue with a ratio of 75%:25% was the most effective in causing mortality of Ae. aegypti within 6 hours.